Does the macroeconomic context influence subjective well-being in Europe and Portugal? The puzzling case of the 2008 crisis - Lopes, H. (2014)
The happiness economics literature shows that, contrary to what happens in the long run, subjective well-being (SWB) and income evolve together in the short term. The aim of the present article is to examine whether this result holds in Europe, and in particular in Portugal, during the 2000s. The empirical study is based on the European Social Survey (ESS) micro-data, merged with Eurostat macroeconomic data (rate of change in GDP, unemployment and inflation). Following the literature, our hypothesis is that self-reported well-being increases in expansionary periods and decreases in recessive ones. Results show that, while the association between well-being and macroeconomic fluctuations are as expected from 2002 to 2008, this is no longer the case when the 2010 data is included in the regression models. In fact, well-being increased in ten out of fifteen European countries after the 2008 crisis. Further examination of the Portuguese data shows that people of all age, education levels, health condition and employment status declared to be happier in 2010 when compared to 2008. Such a puzzling result may be explained by expectations and adaptation processes as well as by an increased awareness, possibly prompted by the crisis, that not only income but also social relationships count in life. Our results thus broadly confirm happiness economics findings: well-being is not exclusively linked with income.